2018
DOI: 10.1590/1981-6723.20717
|View full text |Cite
|
Sign up to set email alerts
|

Moisture sorption isotherms of raw and extruded wholemeal sorghum flours studied by the dynamic and salt slurry methods

Abstract: The saturated salt slurry method has been a standard method for many years, but there are several drawbacks, including long equilibration times, extensive labour and mould growth at high water activity (aw) values. The validity of the dynamic method (automated sorption instrument) was investigated by comparing it with the equilibrium isotherms obtained using the saturated salt slurry method for two food materials (whole sorghum raw flour and whole grain sorghum extrudates), as well as their diffusion coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Galdeano et al. (2018) studied the MSI of raw and extruded wholemeal sorghum flours by using both isopiestic and DVS methods and concluded very close agreement in the results obtained by both the methods for both the products. They reported that the experimentation time of 30 days in case of the static method was reduced to 30 hr using the DVS method.…”
Section: Introductionmentioning
confidence: 80%
“…Galdeano et al. (2018) studied the MSI of raw and extruded wholemeal sorghum flours by using both isopiestic and DVS methods and concluded very close agreement in the results obtained by both the methods for both the products. They reported that the experimentation time of 30 days in case of the static method was reduced to 30 hr using the DVS method.…”
Section: Introductionmentioning
confidence: 80%
“…According to the European Pharmacopoeia classification, MC flour was categorized as a highly hygroscopic material due to its adsorption higher than 15% (w/w) at 25°C, meanwhile, MS and PM were considered as moderately hygroscopic as they reached adsorption values from 2% to 15% at a w = 0.80 at 25°C. due to its typical intermediate moisture (Brunauer et al, 1940;Chen et al, 2017;Galdeano et al, 2018) and is characteristic for nonporous materials or with pores that range from mesopores to macropores. The first inflection point of the isotherm, concave on the a w axis, represents the formation of the monolayer adsorbed on the surface, while the second point, convex on the a w axis, characterizes the adsorption of multiple layers on the surface (Gili et al, 2017;Rahman, 2009).…”
Section: Sorption and Desorption Isothermsmentioning
confidence: 99%
“…The sorption isotherm describes the amount of water sorbed (adsorption or desorption) at equilibrium by a material with known water activity (Aw), constant temperature, and constant pressure (Galdeano et al, 2018).…”
Section: Introductionmentioning
confidence: 99%